2019
DOI: 10.26434/chemrxiv.7995935.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical Exploration of 2,2’-Bipyridines as Electro-Active Compounds in Flow Batteries

Abstract: Molecular information in SMILES code was used as input in Open Babel 2.4.0 \cite{O'Boyle2011} to find the minimum energy conformer using the MMFF94 force field. The generated geometries provided the cartesian coordinates that were used to generate a Gaussian input file. In some cases, it was necessary to apply a preliminary minimization using pseudopotentials (PM7) before performing the actual DFT calculation. Molecular energies of the 156 2,2'-bipirydines were obtained using the Gaussian 16 suite at DFT, with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Comparing against the base structure DQ, E 0 values for 4,4′-DMDQ, 5,5′-DMDQ, and 6,6′-DMDQ derivatives decrease around 0.12 V, this variation is in agreement with that observed upon introducing methyl substituent groups onto the 2,2′-bipyridine core. 33 For (SPr) 2 2− -Vi 2+ and BTMAP +2 -Vi 2+ the opposite behavior is detected; that means, the electron-withdrawing effect of amino and sulfonate groups (having Hammett parameters of 0.86 and 0.30, respectively) 34 cancel the electron-donating abilities of the propyl chain (having a Hammett parameter of −0.06). 34 Then, we examined the MV adsorption process in terms of two theoretical models to shed light on some aspects.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Comparing against the base structure DQ, E 0 values for 4,4′-DMDQ, 5,5′-DMDQ, and 6,6′-DMDQ derivatives decrease around 0.12 V, this variation is in agreement with that observed upon introducing methyl substituent groups onto the 2,2′-bipyridine core. 33 For (SPr) 2 2− -Vi 2+ and BTMAP +2 -Vi 2+ the opposite behavior is detected; that means, the electron-withdrawing effect of amino and sulfonate groups (having Hammett parameters of 0.86 and 0.30, respectively) 34 cancel the electron-donating abilities of the propyl chain (having a Hammett parameter of −0.06). 34 Then, we examined the MV adsorption process in terms of two theoretical models to shed light on some aspects.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A total of 11 exchangecorrelation functionals, also including some of the D3 dispersion 59,60 corrected variants, are used for high-level OPT and SPE calculations. These functionals include LDA 57 , PBE 40,61 , PBE-D3 59 , BLYP 62 , BLYP-D3 59 , B3LYP 62,63 , B3LYP-D3 59 , PBE0 64 , PBE0-D3 59 , HSE06 65 , and M08-HX 39 . Due to computational costs, the DFT aqueous-phase geometry optimizations are performed only with the following functionals: PBE, B3LYP, and M08-HX.…”
Section: Computational Detailsmentioning
confidence: 99%
“…27,28 In addition, it has also been investigated as a candidate energy storage compound. 29 For the backbone structures with 5-membered rings (7)(8)(9)(10)(11)(12)(13)(14), the single C atoms that are positioned between the two N atoms of 2H-imidazole (7) and 2H-benzimidazole (11) molecules were substituted in turn with N, S, and O atoms, thereby generating two subsets (8-10 and 12-14) of heterocyclic backbones. The rest of the backbone structures (15-31) contain only 6membered rings, and were created by using the Elemental Enumeration tool of the Schrödinger Materials Science Suite (SMSS).…”
Section: Molecular Library Designmentioning
confidence: 99%
“…We found that the redox potentials of single ring backbone structures, 15 and 16, are quite similar to each other. However, they are spread over a wider range for molecules with two (17)(18)(19)(20)(21)(22) and three rings (23)(24)(25)(26)(27)(28)(29)(30)(31). The solvation energies for the backbone structures are also found to be a complex function of the size of the molecules and the distance between the backbone nitrogen atoms.…”
Section: Structure-property Relationshipsmentioning
confidence: 99%